Civil Servant Behavior in Public Service Delivery: A Qualitative Case Study: JEL Classification: H83, D73, J45, M14, M12 - Yosar Kardiat (Journal La Bisecoman, 2026)
This paper will be analyzing the dynamics of civil servant behavior in the delivery of services in Gowa Regency, Indonesia. It is based on the fact that service quality is determined not only by the formal procedures but also by how the civil servants interpret their jobs, react to their citizens, exercise discretion and work within the organizational and managerial environments. The study was based on a qualitative case study design and the population was selected purposely and included frontline civil servants, managerial officials, and community citizens who had direct exposure to the services of the population. The information was gathered via in depth interviews, non-participant observation and data analysis using themes, and was then analyzed using thematic analysis. The results show that the behavior of civil servants is created in a negotiation process between the official rules of administration and the realities that people face in their daily lives. The discretion was found to be empowering and dangerous, in a sense that it can make it more responsive, but it may bring inconsistencies where there is no mutual basis and certain direction. The research also found out that organizational culture, bureaucratic environment and leadership have a strong impact on service behavior in the sense that they influence coordination, communication, confidence and responsibility. In conclusion, the research finds that improvement of the public service must not be restricted to the change of procedures but also a favorable organizational culture and leadership that is able to maintain the same responsive and ethically based service behaviour.